The effect of vitamin C on bronchoconstriction and respiratory symptoms caused by exercise: a review and statistical analysis - Hemilä, Harri (Allergy Asthma Clin Immunol, 2014)
Physical activity increases oxidative stress and therefore the antioxidant effects of vitamin C administration might become evident in people undertaking vigorous exercise. Vitamin C is involved in the metabolism of histamine, prostaglandins, and cysteinyl leukotrienes, all of which appear to be mediators in the pathogenesis of exercise-induced bronchoconstriction (EIB). Three studies assessing the effect of vitamin C on patients with EIB were subjected to a meta-analysis and revealed that vitamin C reduced postexercise FEV(1) decline by 48% (95% CI: 33% to 64%). The correlation between postexercise FEV(1) decline and respiratory symptoms associated with exercise is poor, yet symptoms are the most relevant to patients. Five other studies examined subjects who were under short-term, heavy physical stress and revealed that vitamin C reduced the incidence of respiratory symptoms by 52% (95% CI: 36% to 65%). Another trial reported that vitamin C halved the duration of the respiratory symptoms in male adolescent competitive swimmers. Although FEV(1) is the standard outcome for assessing EIB, other outcomes may provide additional information. In particular, the mean postexercise decline of FEF(50) is twice the decline of FEV(1). Schachter and Schlesinger (1982) reported the effect of vitamin C on exercise-induced FEF(60) levels in 12 patients suffering from EIB and their data are analyzed in this paper. The postexercise FEF(60) decline was greater than 60% for five participants and such a dramatic decline indicates that the absolute postexercise FEF(60) level becomes an important outcome in its own right. Vitamin C increased postexercise FEF(60) levels by 50% to 150% in those five participants, but had no significant effect in the other seven participants. Thus, future research on the effects of vitamin C on EIB should not be restricted to measuring only FEV(1). Vitamin C is inexpensive and safe, and further study on those people who have EIB or respiratory symptoms associated with exercise is warranted. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1710-1492-10-58) contains supplementary material, which is available to authorized users.